ILRAD 1993. Annual scientific Report - International Laboratory for Research on Animal Diseases (International Laboratory for Research on Animal Diseases, 1994)
This volume presents summaries of the scientific activities of the International Laboratory for Research on Animal Diseases (ILRAD) for 1993. Research at ILRAD is managed on a project basis and the abstracts are numbered according to their relation to projects in each of the programmes, viz., the Tick-Borne Diseases Programme, the Trypanosomiasis Research Programme and the Socio-economics Research Programmes. The full titles of the projects are given on the Table of Contents page and abridged versions are given as running heads on each page of the collected abstracts. Each project also indicates the involved scientist and technicians. The projects covers topics like diagnosis, epidemiology, parasite genetics, characterization, transmission, immunization, genome analysis, parasite differentiation, antigens, chemotherapy and evaluation.